Expression of immunophenotype, inflammatory response and chromosomal abnormality in acute lymphoid leukemia - Nguyen, Hoang Giang; Vu, Xuan Nghia; Do, Thi Trang; Nguyen, Thi Xuan (Vietnam Journal of Biotechnology, 2026)
Acute lymphoblastic leukemia (ALL) is the most common childhood malignant hematologic disease characterized by the uncontrolled accumulation of lymphoid progenitor cells within the bone marrow and peripheral blood. According to the World Health Organization (WHO) classification and National Comprehensive Cancer Network (NCCN) guidelines, ALL patients are classified into two main risk groups, including standard-risk and poor-risk groups based on clinical and biological features, including age at diagnosis, white blood cell count, cytogenetic abnormalities, and early treatment response. Inflammation-related genes, such as tumor necrosis factor-α (TNFα)-induced protein 3 (TNFAIP3, A20), tumor suppressor cylindromatosis (CYLD) and Cezanne genes, are negative regulators of immune cell activation, and cell survival. To this end, 57 patients diagnosed with ALL and 30 healthy subjects were enrolled. Immunophenotype was determined by flow cytometry, gene expression and chromosomal abnormalities by quantitative PCR, and secretion of cytokines by ELISA. As a result, the poor-risk group had age-related higher levels of lactate dehydrogenase (LDH), white blood cell, lymphocytes and neutrophil counts than the standard-risk group. Cytokine analysis revealed that transforming growth factor beta (TGF-β) levels were markedly increased in the poor-risk group. In addition, expression levels of CYLD, A20, and Cezanne genes were not significantly different between the two groups, although CYLD levels tended to be lower in the poor-risk group. Importantly, p210 BCR-ABL and p190 BCR-ABL fusion transcripts were detected more frequently in poor-risk patients. In conclusion, this study indicates that age-related numbers of malignant lymphoid cells, but not inflammatory expression, were associated with poor outcomes in ALL patients.